ATRAKTOR CUMI-CUMI, SEBAGAI SARANA ALTERNATIF PEMBERDAYAAN NELAYAN BERKELANJUTAN DI REUGAIH KABUPATEN ACEH JAYA - Farah Diana; Muhammad Rizal (JURNAL PERIKANAN TROPIS, 2015)
Development of appropriate consept is needed as effort to maintain the carrying capasity of the environment in the Rigaih region.Squid attractor is one of  tools to incresing carrying capasity of fish resources and it can preserving in order to develop the coastal areas in an integrated and sustainable. This study aims to a) preservation of ecosystem with breading squid b)one of tools for integrated and sustainable fishing at Rigaih.Methods of the study as follow: a ) squid attractor is simple designed, i.e. like flower with diameter is 100 cm and high is30 cm. Material of attractors is plastic wire with strands of rope and at the top is covered by black plastic. Untaian tali-tali tambang yang dipasang pada bagian dalam atraktor ini berfungsi sebagai tempat cumi-cumi menempelkan telurnya.Lokasi pemilihan pemasangan atraktor ini ditentukan bersama Panglima Laot Rigaih dan nelayan setempat dengan pemasangan di dalam perairan dilakukan secara sistem rangkaian yang panjang, dimana satu lokasi dapat terdiri dari sepuluh atraktor dengan jarak antar atraktor 15 m; b) Installation distance between attarctors is 15 m; c) observation squid egg. Result of the study have been show that squid attractor very suitable for preserving squid andit is able to increasing income of fisherman at Rigaihin the future.